Downlink capacity improvement of WCDMA system by using adaptive antenna with novel MDPC beamforming technique - Tiong, Sieh Keong; Koh, Johnny; Ismail, Mahamod; Hassan, Azmi (Electronic Design, Test and Applications, Third IEEE International Workshop on, 2006)
Smart antenna is a well known method to increase the spectral efficiency of the wireless channel and subsequently increase the mobile communication system capacity without jeopardizing the system QoS [1][2]. There are two major types of smart antenna systems; switch beam antenna and adaptive beam antenna. Adaptive antenna which has dynamic beam to cater for users needs is better in improving the system capacity but requires more advance beam forming algorithm and requires intensive processing power for beam forming. Thus, adaptive beam forming technique is critically important. In this paper, a novel adaptive downlink beam forming technique for WCDMA system namely Minimum Downlink Power Consumption (MDPC) is introduced. A dynamic radio network simulator was developed in Visual C++® to study the power consumption at WCDMA base station (Node B) and to estimate the downlink capacity improvement by implementing this novel algorithm. Simulation was done based on a single micro cell environment with consideration of interference from the first tier. User mobility is taken into account to provide a combined evaluation of Radio Resource Management (RRM). Capacity system expressed in downlink outage under various simulation scenarios was represented in this paper.